(untitled) (El-Wahat Journal for Research and Studies, 2025)
French-Language Algerian Novels Assiduously Develop Reflections On Social Issues, The Religious And The Political. In Khalil, Yasmina Khadra Again Addresses The Religious Fact In His Story, An Evocation Serving To Explain And Correct The Stereotypes That Blacken The Minds. In The Present Study, An Exploration, Via A Paratextual And Sociocritical Study Of The Khadrien Text Will Take Place In Order To Show The Presence Of The Religious Fact And The Way In Which It Is Presented. Keywords: Religious Story, Islam, Sociocritism, Religious Experience, Character.